Delayed primary excision with subsequent modification of radiotherapy dose for intermediate‐risk rhabdomyosarcoma: A report from the Children's Oncology Group Soft Tissue Sarcoma Committee. Issue 1 (10th December 2014) - Rodeberg, David A.; Wharam, Moody D.; Lyden, Elizabeth R.; Stoner, Julie A.; Brown, Kenneth; Wolden, Suzanne L.; Paidas, Charles N.; Donaldson, Sarah S.; Hawkins, Douglas S.; Spunt, Sheri L.; Arndt, Carola A.
Abstract : The majority of intermediate‐risk rhabdomyosarcoma (RMS) patients have gross residual disease (Group III) after their first operative procedure. It is currently not known if local control rates can be maintained when, following induction chemotherapy, the radiation therapy (RT) dose is decreased after a delayed primary excision (DPE). To answer this question we evaluated patients enrolled on COG D9803 (1999–2005) who had Group III tumors of the bladder dome, extremity or trunk (thorax, abdomen and pelvis) were candidates for DPE at Week 12 if the primary tumor appeared resectable. RT dose was then adjusted by the completeness of DPE: no evidence of disease 36 Gy, microscopic residual 41.4 Gy and gross residual disease (GRD) 50.4 Gy. A total of 161 Group III patients were evaluated (24 bladder dome, 63 extremity and 74 trunk). Seventy‐three patients (45%) underwent DPE which achieved removal of all gross disease in 61 (84%) who were then eligible for reduced RT dose (43/73 received 36 Gy, 19/73 received 41.4 Gy). The local 5‐year failure rate (0% for bladder dome, 7% for extremity and 20% for trunk) was similar to IRS‐IV, which did not encourage DPE and did not allow for DPE adapted RT dose reduction. In conclusion, DPE was performed in 45% of Group III RMS patients with tumors at select anatomic sites (bladder dome, extremity and trunk) and 84% of those who had DPE were eligible for RT dose reduction. Local control outcomes were similar to historic results with RT alone. Abstract : What's new? Over the course of their lives, about half of individuals who survive childhood sarcoma experience one or more adverse outcomes associated with the treatment of their malignancy. As a result, there is significant need for the investigation of less‐toxic therapeutic strategies for pediatric cancers. This study shows that among pediatric patients with rhabdomyosarcoma (RMS), dose reduction in radiotherapy (RT) is feasible following delayed primary excision (DPE), with RT dosage determined by completeness of resection. Local control outcomes with RT dose reduction following DPE were comparable to those reported for a similar population of RMS patients treated with radiotherapy alone.